Traditional agro-ecosystems in Southern Philippines: Vulnerabilities, threats and interventions. Issue 4 (29th August 2019) - Zapico, Florence; Hernandez, Jose; Borromeo, Teresita; McNally, Kenneth; Dizon, Josefina; Fernando, Edwino
Abstract : Purpose: Sarangani, a province in Southern Philippines, is inhabited predominantly by tribal groups who depend on traditional rice farming for subsistence and livelihood. The purpose of this study is to identify current pressures to these upland communities and the interventions instituted to address them or mitigate their effects. Design/methodology/approach: This is an exploratory and cross-sectional research using the emic approach. Rapid rural appraisal techniques (i.e. focus group discussion, key informant interviews, community immersion and field observation) were concurrently undertaken in 15 farming villages in the Sarangani uplands. Findings: Results revealed that many upland families inhabited disaster-prone areas under conditions of hardship and abject poverty. Prevalent problems in these areas have largely arisen from the encroachment of modern agriculture, environmental degradation and changes in the socio-political and economic spheres. Consequently, food insecurity, cultural and genetic erosion and biodiversity losses have resulted in lowered Sarangani agro-ecosystem resilience. While policies and programs had been instituted to address these problems, positive results still remain to be realized. Social implications: Weak social networks in the Sarangani upland communities are attributable to their isolation and the disruptive influences of modernization. Agricultural modernization, in particular, caused the disintegration of community social structures and undermined overall well-being of the farmers. Sustainable strategies which harmonize modern and traditional systems of food production and environmental management are warranted to attain food security, environmental preservation and bio-cultural preservation. Originality/value: This study contributes to the present body of knowledge about threats to vulnerable agro-ecosystems inhabited mainly by indigenous tribes. And while only 15 farming villages were covered by the study, these results can serve as a microcosm of what is happening in traditional agro-ecosystems worldwide. The study is also expected to provide inputs to policymakers, which they can use in crafting policies to address problems in the Sarangani uplands.